2017
DOI: 10.1080/09593330.2017.1400110
|View full text |Cite
|
Sign up to set email alerts
|

A combination of absorption and enzymatic biodegradation: phenol elimination from aqueous and organic phase

Abstract: Peroxidase from Brassica rapa was immobilized as cross-linked enzyme aggregates (CLEAs) and used to treat air containing phenol as a model molecule of volatile organic compounds (VOCs). Prior to an enzymatic treatment, phenol was absorbed into an aqueous or organic phase (silicone oil) to reach concentrations ranging from 20 to 160 mg/L. The process was carried out by introducing a desired weighing of BRP-CLEAs into preparations and reaction was started by injecting HO solution to the medium. Optimization of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…A dramatic decrease in phenol degradation (65% of conversion yield with a degradation rate of 1.6 mg.L -1 .min -1 ) occurred when enzyme dose decreased to 0.45 U.mL -1 . This might be justified by a decrease in the availability of active sites ready to with the target compound (Tandjaoui et al, 2019). The experiments also revealed that a lower amount of CLEAs was sufficient to achieve more than 98% of p-cresol degradation J o u r n a l P r e -p r o o f (Fig.…”
Section: Effect Of Rsvnp-cleas Activity On Phenols Removalmentioning
confidence: 96%
“…A dramatic decrease in phenol degradation (65% of conversion yield with a degradation rate of 1.6 mg.L -1 .min -1 ) occurred when enzyme dose decreased to 0.45 U.mL -1 . This might be justified by a decrease in the availability of active sites ready to with the target compound (Tandjaoui et al, 2019). The experiments also revealed that a lower amount of CLEAs was sufficient to achieve more than 98% of p-cresol degradation J o u r n a l P r e -p r o o f (Fig.…”
Section: Effect Of Rsvnp-cleas Activity On Phenols Removalmentioning
confidence: 96%
“…With the leakage of organic solvents (OSs) in the process of transportation, offshore oil exploitation and industrial oily wastewater discharge, the aquatic environment has been seriously damaged (Li et al 2019a;Simha et al 2018). At present, a variety of methods have been used to separate OSs from water, including adsorption (Benally et al 2019;Brusseau 2019;Meng et al 2019), flocculation (Vandamme et al 2018), membrane separation (Zhao and Chung 2018), solvent extraction (Chang 2020), biodegradation (Tandjaoui et al 2019;Wang et al 2018a, b), in-situ combustion (Xiang et al 2018) and solidification (Jia et al 2019). The adsorption method is given priority due to its low cost, easy operation and fast response, which is widely regarded as an effective choice for treating OSs-bearing wastewater (Benally et al 2019;Li et al 2019b;Wu et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Generally present in natural waters at concentration levels around pg L -1 and not exceeding ng L -1 , it is however often found at concentrations ranging from 7.6 µg L -1 to 9.9 µg L -1 in wastewater from petroleum refineries (Wang et al, 2019). Similarly, the atmosphere is also affected by the pollution problem and for this reason, the European Commission (EC) legislations and regulations on air quality and waste air treatment are more prevalent in terms of management and control industrial waste (Tandjaoui et al, 2019). A large number of Volatile Organic Compounds (VOCs) 6 constitute a significant part of air pollution and are directly responsible for greenhouse effect, stratospheric ozone depletion and photochemical smog (Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%